Digitally connected, evolutionarily wired: An evolutionary mismatch perspective on digital work - VAN VUGT, Mark (Institutional Knowledge at Singapore Management University, 2024)
This paper makes the case for an evolutionary mismatch between digital work and the way human ancestors engaged in work. Psychological adaptations for producing things that early humans needed to survive and thrive, such as cognitive mechanisms for obtaining and processing food, toolmaking, and learning valuable working skills, evolved in the context of small networks of hunter–gatherers. These adaptations are central to understanding the significance of work in human evolution. Evolutionary mismatches operate when novel environments cue ancestral adaptations in ways that no longer provide adaptive benefits. We argue that digital work, although efficient and productive, is misaligned with some fundamental human needs, preferences, and routines, thereby illuminating a potential dark side. Yet digitalization also offers opportunities for matching the modern work environment to our evolved work psychology. We conclude with an agenda for advancing research in industrial and organizational psychology on digital work from an evolutionary mismatch perspective.